Point-Prevalence Survey for the Hospital-Acquired Infections and Infection Prevention and Control Status of Different Wards of Rajshahi Medical College Hospital (TAJ: Journal of Teachers Association, 2023)
Introduction: Healthcare-associated infections represent significant obstacles to providing high-quality healthcare and have been directly linked to ineffective infection control procedures. There is currently a shortage of trustworthy data in Bangladesh describing the epidemiology of hospital-acquired infections (HAIs), which is necessary for the development of effective infection prevention and control measures. This study's goal was to assess the frequency, nature, and risk factors of HAIs in acute care hospitals in Northern Bangladesh.Methods: This was a pilot point prevalent survey conducted in the medicine, surgery, gynecology, and obstetrics departments of Rajshahi Medical College Hospital between August 2022 to September 2022. Data were collected by two questionnaires for disease profile and hospital-acquired infection. In addition, a checklist was used for the observation of the infection prevention and control (IPC) status of different wards.Result: Approximately 900 patients' data were collected during this time period. The overall prevalence of HAI was found to be 3.7%. The prevalence of HAI, especially surgical site Infection (SSI), in the obstetrics ward, was 4.2%, and the Medicine ward was 3.9%, respectively. The prevalence of hospital-acquired infection in the surgery ward is 7.7%. Approximately 41.7% of patients developed SSI on the 6th post operative day (POD). The Infection prevention and control status of different wards was similar, which was not satisfactory.Conclusion: This surveillance might help concerned authorities and policymakers by making some crucial steps to monitor and reduce hospital-acquired infections and HAIs in hospitals.TAJ 2022; 36: No-1: 9-15